Scarf’s generalization of linear complementarity problem revisited - Neogy S.K.; Sinha S.; Das A.K.; Gupta A. (Yugoslav Journal of Operations Research, 2013)
In this paper, we revisit Scarf’s generalization of the linear complementarity problem, formulate this as a vertical linear complementarity problem and obtain some new results on this generalization. Also, a neural network model for solving Scarf’s generalized complementarity problems is proposed. Numerical simulation results show that the proposed model is feasible and efficient.